New experimental and theoretical assessment of the dissociation energy of C2. (3rd July 2019) - Visser, Bradley; Beck, Martin; Bornhauser, Peter; Knopp, Gregor; van Bokhoven, Jeroen Anton; Radi, Peter; Gourlaouen, Christophe; Marquardt, Roberto
ABSTRACT: The dissociation energy in the X 1 Σ g + electronic ground state of the carbon dimer C 2 is determined spectroscopically from a combined treatment involving resonant four-wave mixing experiments and highly accurate multi-reference configuration interaction calculations to be ( 50 370 ± 150 ) h c cm − 1 ( ( 6.24 ± 0.02 ) eV, ( 602 ± 2 ) kJ mol −1 ). This new value allows us to clarify current discrepancies among other experimental and theoretical results, which will be discussed. GRAPHICAL ABSTRACT: